An Empirical Investigation of Nurse Retention through Integrating Quality of Nurses Work-Life, HRM Practices, Employee Happiness, and Electronic Health Record System among Jordanian Nurses - Gharaibeh, Muna Bassam Abdel Rahman; Dato Mansor, Zuraina binti; Yusof, Raja Nerina binti Raja (Journal of Entrepreneurship, Business and Economics; Vol 13 No 2 (2025), 2025)
This study aimed to investigate the impact of the quality of nurse work retention and HRM practices on nurse retention in the mediation role of employee happiness while moderating the role of the electronic health record system. This study used two theories: sociotechnical systems and social exchange. The data were collected from 419 nurses of public and university hospitals in Jordan. The collected data was analysed through the structural equation modeling technique by using SmartPLS 3.0. The findings reveal that both QNWL and HRM practices positively impact nurse retention. Also, the mediation role of employee happiness between HRM practices and nurse retention is significant. However, the positive impact of performance appraisal on nurse retention is not supported. Also, the moderating role of EHRS on the relationship of QNWL and nurse retention is not supported. This study provides theoretical and practical insights regarding improving nurse retention and offers a comprehensive framework for healthcare institutions. Research Paper Keywords: Nurse retention, quality of nurse work life (QNWL), HRM practices, employee happiness, electronic health record system, Jordan Reference to this paper should be made as follows: Gharaibeh, M.B.A.R., Dato Mansor, Z.B., & Yusof, R.N.B.R. (2025). An Empirical Investigation of Nurse Retention through Integrating Quality of Nurses Work-Life, HRM Practices, Employee Happiness, and Electronic Health Record System among Jordanian Nurses. Journal of Entrepreneurship, Business and Economics , 13 (2), 1–53.